THE INFLUENCE OF AWARENESS, UNDERSTANDING, AND SERVICE QUALITY ON COMPLIANCE WITH PAYING TAXES AT THE TAX OFFICE PRATAMA WEST MATARAM - M. Wahyullah; Baiq Kisnawati; Aulia Rizki (ShariaBiz International Journal of Economics & Business, 2024)
This study aims to determine the effect of awareness of individual taxpayers, level of understanding of taxpayers, and quality of tax services on the level of compliance in paying individual taxpayers' taxes at Tax Office Pratama West Mataram. The independent variables in this study are individual taxpayer awareness, taxpayer understanding, and tax service quality, while the dependent variable is tax compliance. The population in this study consisted of individual taxpayers, with a total of 148,228 taxpayers at the Tax Office Pratama West Mataram. This study uses primary data by distributing questionnaires. One hundred questionnaires were distributed to individual taxpayers at the Tax Office Pratama West Mataram. The research sample was taken using a convenience sampling method. Data analysis used multiple regression analysis. The results show that the understanding of taxpayers does not affect taxpayer compliance. At the same time, the awareness of individual taxpayers and the quality of tax services significantly affect individual taxpayers' compliance with the Tax Office Pratama West Mataram.